Autonomous learning among Vietnamese EFL students: A case study at Thu Dau Mot University - Nguyen, Thanh Thai (Technium Social Sciences Journal, 2026)
Learner autonomy has been widely recognized as a key factor in successful language learning; however, its development remains challenging in many EFL contexts. This study investigates autonomous learning among undergraduate EFL students at Thu Dau Mot University, Vietnam. Specifically, it examines students’ awareness of learner autonomy, identifies the difficulties they encounter, and explores the strategies they employ to enhance their self-directed learning. A mixed-methods approach was adopted, with data collected from 120 first-year English-major students through a structured questionnaire. Quantitative data were analyzed using descriptive statistics, while qualitative responses provided additional insights into students’ perceptions. The findings reveal that most students demonstrate a high level of awareness regarding the importance of autonomous learning, with over 80% acknowledging its impact on academic achievement and 88% reporting engagement in self-directed learning. However, a substantial proportion of students experience difficulties in practicing autonomy, particularly due to a lack of effective learning strategies, insufficient planning skills, low motivation, and limited access to learning resources. Although students reported using strategies such as self-control and goal-setting, these were applied inconsistently. The study highlights a significant gap between students’ awareness and actual practice of learner autonomy. It suggests that enhancing metacognitive skills, providing structured pedagogical support, and improving learning resources are essential to fostering effective autonomous learning among university EFL students.